Bridging Challenges and Expectations: Effective Strategies for Teaching English Speaking Skills to Slow Learners - Rahayuni, Dwi Nurhayati; Karimullah, Imam Wahyudi; Elfiyanto, Sonny (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2025)
Every child born regardless of physical and mental condition has the right to receive a proper education. The right to education is a basic right that must be obtained by all children, including children with special needs. Recently, special need students can not only receive education through special schools but they can attend public schools side by side with regular students. The teacher's treatment in delivering material to special need students is certainly not the same as the treatment to regular students. Special assistant teachers have a very important role in assisting material to special need students. This research aims to examine the strategies used by teachers in delivering material, as well as the challenges and expectations in learning English for students with special needs. The research method used was direct interviews and surveys. The respondents are special assistant teachers and special need students. The results show that special assistant teachers have several teaching strategies. Although they face many challenges in applying the strategies, they can achieve the desired expectations. The strategies used show their effectiveness. It can be proven by the ability of special need students to apply the material received and put it into practice.